Enhanced Performance of Ternary CuGaSe2 Thin‐Film Photovoltaic Solar Cells and Photoelectrochemical Water Splitting Hydrogen Evolution with Modified p–n Heterointerfaces. Issue 25 (2nd August 2022) - Ishizuka, Shogo; Okamoto, Riku; Ikeda, Shigeru
Abstract: Renewable energy sources, in particular, photovoltaic solar cells and hydrogen fuel, are expected to be the pillars of a sustainable society. Chalcopyrite CuGaSe2 (CGSe) has potential for using in such applications. This article presents efficient solar cells suitable as top cells for tandem devices and highly active photocathodes for solar hydrogen evolution using CGSe photoabsorber layers with modified p–n heterointerfaces. Rb‐doping during the last stage of CGSe film growth effectively improves the photovoltaic performance, and solar cell efficiency of >10% with a high fill factor (FF) of 74.6% is obtained. The half‐cell solar‐to‐hydrogen conversion efficiency reaches 8% with the use of a photocathode composed of a CGSe film grown in an identical growth batch. Interface modification with i) a Cu‐deficient layer, ii) alkali‐metal doping, and iii) an n‐type buffer layer formed on the CGSe film surface is found to a be key to control the energy conversion device parameters, such as the FF and open circuit voltage of solar cells and the onset potential of photoelectrochemical cells, due to the suppression of interface recombination. Abstract : Dual‐use of wide bandgap chalcogenide thin‐films in photovoltaic solar cells and photoelectrochemical water splitting hydrogen evolution is possible. This article presents efficient photovoltaic solar cell and hydrogen evolution using CuGaSe2 ‐based photoabsorber layers with surface/interface modification using Cu‐deficient phases, alkali‐metal doping, and an n‐type buffer material.